TEACHING FOREIGN LANGUAGES AT THIRD-YEAR STUDENTS IN POLAND - Ivashko, Olena (The Modern Higher Education Review, 2019)
The article tackles the problem of teaching foreign languages to seniors. The general trends in FL education for the third-age learners are outlined. The institutions in which seniors can study foreign languages in Poland are enumerated. The psychological, physiological, methodological and social peculiarities of teaching a foreign language to the third agers are analyzed. Special emphasis is laid upon educational needs of the Third Age learners. Some language learning strategies which help seniors’ foreign language learning are suggested.